Stability and Thermoelasticity of Diaspore by Synchrotron X-ray Diffraction and Raman Spectroscopy - Huang, Shijie; Xu, Jingui; Liu, Daorong; Li, Bo; Ye, Zhilin; Chen, Wei; Kuang, Yunqian; Chi, Fangli; Fan, Dawei; Ma, Maining; Zhou, Wenge (Frontiers in Earth Science, 2021)
The thermoelasticity and stability of diaspore (α-AlOOH, Al1.002Fe0.003OOH) were investigated in this study by in situ synchronous X-ray diffraction (XRD) and Raman spectroscopy methods at high pressure and high temperature conditions. The results indicate that diaspore is stable within the pressure and temperature (P-T) region examined in this study. With increasing pressure, the Raman peaks move toward the high wave number direction, the intensity of the Raman peaks increases, and the vibration mode of diaspore changes linearly. Pressure-volume data from in situ high-pressure XRD experiments were fitted by the third-order Birch-Murnaghan equation of state (EoS) with the zero-pressure unit-cell volume V0 = 118.15 (4) Å3, the zero-pressure bulk modulus KV0 = 153 (2) GPa, and its pressure derivative K'V0 = 2.4 (3). When K'V0 was fixed at 4, the obtained KV0 = 143 (1) GPa. The axial compressional behavior of diaspore was also fitted with a linearized third-order Birch-Murnaghan EoS, showing slight compression anisotropy with Ka0 =137 (5) GPa, Kb0 = 169 (7) GPa and Kc0 = 178 (6) GPa. In addition, the temperature-volume data from in situ high-temperature XRD experiments were fitted by Fei’s thermal equation with the thermal expansion coefficients αV = 2.7 (2)×10-5 K-1, αa = 1.13 (9)×10-5 K-1, αb = 0.77 (5)×10-5 K-1, and αc = 0.85 (9)×10-5 K-1 for diaspore, which shows that diaspore exhibits slightly anisotropic thermal expansion. Furthermore, in situ synchrotron-based single-crystal XRD under simultaneously high P-T conditions indicates that the P-T stability of diaspore is up to ~10.9 GPa and 700 K. Combined with previous results, we infer that diaspore can be subducted to ~370 km under cold subduction conditions and is a good candidate for transporting water to the deep Earth.